2022
DOI: 10.3390/cancers14133164
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Immune Checkpoint GPR56 Is Expressed on Tumor-Infiltrating Lymphocytes and Selectively Upregulated upon TCR Signaling

Abstract: High levels of tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment (TME) are associated with a survival benefit in various cancer types and the targeted (re)activation of TILs is an attractive therapeutic anti-cancer approach that yields curative responses. However, current T cell targeting strategies directed at known immune checkpoints have not increased objective response rates for all cancer types, including for epithelial ovarian cancer (EOC). For this reason, the identification of new imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…Different studies revealed that during chronic LCMV infection, Adgrg1 is expressed much higher in T cells possessing an advanced state of exhaustion (Figure 2B). 44,45,47 In line herewith, ADGRG1 expression is upregulated in terminally exhausted CD8 + tumour‐infiltrating lymphocytes in human 37 . Thus, in sum, T EMRA and T RM cells express GPR56 and further upregulate the receptor when entering a state of exhaustion.…”
Section: Cytolytic Lymphocytes Express Gpr56/adgrg1supporting
confidence: 65%
See 2 more Smart Citations
“…Different studies revealed that during chronic LCMV infection, Adgrg1 is expressed much higher in T cells possessing an advanced state of exhaustion (Figure 2B). 44,45,47 In line herewith, ADGRG1 expression is upregulated in terminally exhausted CD8 + tumour‐infiltrating lymphocytes in human 37 . Thus, in sum, T EMRA and T RM cells express GPR56 and further upregulate the receptor when entering a state of exhaustion.…”
Section: Cytolytic Lymphocytes Express Gpr56/adgrg1supporting
confidence: 65%
“…36 Moreover, in a wide range of tumour types, infiltrating T cells express GPR56. 37 While human CD56 dim CD16 + NK and T EMRA cells have the ability to retain granzyme B protein expression into the memory phase, mice may not have an exact correlate of these cells. Accordingly, mice lack circulating NK and T cells expressing GPR56 (www.immgen.org) (Figure 2A).…”
Section: Cytolytic Lymphocytes Express Gpr56/adgrg1mentioning
confidence: 99%
See 1 more Smart Citation
“…In a different disease setting, single-cell transcriptomic (scRNAseq) analysis of a tumor immune cell atlas dataset showed that GPR56 mRNA transcripts are expressed predominantly in CD8 + tumor-infiltrating lymphocytes (TILs) that displayed a (pre)exhausted and tumor-reactive phenotype [ 133 ]. As such, elevated GPR56 protein expression was detected in TILs of ovarian cancer patients and these GPR56-expressing TILs were mostly associated with the effector memory (T EM ) and central memory (T CM ) phenotypes.…”
Section: Adgrg1/gpr56mentioning
confidence: 99%
“…As such, elevated GPR56 protein expression was detected in TILs of ovarian cancer patients and these GPR56-expressing TILs were mostly associated with the effector memory (T EM ) and central memory (T CM ) phenotypes. Finally, enforced GPR56 expression inhibited in vitro migration of primary T cells in response to SDF-1 [ 133 ]. Similarly, transcriptomic profiling of tumor-infiltrating neoantigen-reactive T cells of gastrointestinal cancer patients delineated an exhausted phenotype in the majority of CD8 + and CD4 + neoantigen-reactive TILs and showed that GPR56 was up-regulated significantly in CD4 + neoantigen-reactive TILs [ 134 ].…”
Section: Adgrg1/gpr56mentioning
confidence: 99%